Antioxidant regulatory mechanisms in neutrophils and lymphocytes after intense exercise - Ferrer, M. D.; Tauler, P.; Sureda, A.; Tur, J. A.; Pons, A. (Journal of Sports Sciences, 2009)
The aims of this study were to assess the effects of a swimming session on the peripheral blood neutrophil and lymphocyte pro- and antioxidant system, identify any differences between the sexes and the regulatory mechanisms that might induce the immune cell adaptive response to exercise. Twenty-four swimmers (15 males, 9 females) participated in a one-hour swimming session at 75-80% of their maximal capacity. The session induced neutrophilia and decreased antioxidant enzyme activities and ascorbate levels in neutrophils. Malondialdehyde rose in neutrophils in males and females, whereas the carbonyl index only increased in males. Lymphocyte glutathione peroxidase activity was higher in males at baseline and rose as a consequence of exercise. The exercise decreased uncoupling protein-3 and Bcl-2 gene expression. The expression of PPAR? coactivator-1 alpha (PGC-1) correlated positively with that of sirtuin 3 (SIRT3) and catalase. In summary, a swimming session of one hour at 75-80% of maximal capacity produced oxidative damage in neutrophils and induced the antioxidant defences in lymphocytes. PGC-1 and SIRT3 appear to be key effectors of this adaptive response in lymphocytes. Both the neutrophil and lymphocyte response to exercise were slightly weaker in females than males.